Method for Measuring Damage to Viability and Morphology of Spermatozoa in Experimental Animals After Exposure to Cigarette Smoke - Muksin, Yufika Dewi; Mahrus, Mahrus; Bahri, Syamsul (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Smokers in Indonesia are ranked first in the world and the biggest cause of death. Free radicals contained in cigarette smoke cause condensation of the structure of the genetic material of sperm cells and lead to sperm cell death (apoptosis). The aim of the research was to determine the effect of cigarette exposure and its interactions on the quality of spermatozoa in experimental animals. This research is a laboratory experiment with a Completely Randomized Factorial Design. The samples in this study were 60 males of the Balb/C strain which were divided into 5 treatment groups. Each treatment group was given concentrations of red dragon fruit peel extract including 0%, vitamin C, 50 µg/mL, 500 µg/mL, and 5000 µg/mL and were exposed to cigarette smoke. Analysis of research results used the Two Way ANOVA test at a significance level of 0.05. The results of the study showed that there was an effect of exposure to cigarettes and administration of red dragon fruit peel extract on the sperm quality of mice. The highest exposure to cigarette smoke was given to red dragon fruit peel extract in terms of viability of 89% and morphology of 93.33%. Administration of red dragon fruit peel extract reduced the effect of exposure to cigarette smoke on the viability and morphology of mice.